“An Analysis of Emotional Meaning in John Lennon’s “Imagine” through Halliday’s Systemic Functional Linguistics” - Musthafa Kemal Pasha; Yusmar Amalia Soleha; Sabriena Dhea Azzahra; Mayang Sandyo Anggoro (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2026)
This study used the Systemic Functional Linguistics (SFL) approach to analyze the emotional value of John Lennon's song "Imagine," with a priority on the ideational, interpersonal, and textual metafunctions. The goal of this study is to comprehend how Lennon expresses his feelings, ideals, and aspirations for global peace through language. Based from research, Lennon uses both material and mental processes to explain his vision of a world without conflict, and his interpersonal decisions particularly those related to mood and modality show his empathy and emotional attachment to his audience. The melody's literary structure, which is based on theme arrangement and repetition, strengthens the message of equality and harmony.